Estimation of bacterial number in the water, sediment and biofilm of Badek and Mewek River (Malang, Indonesia) using Plate Count and eDNA Method - Devi Ulinuha; Sri Andayani; Asus Maizar Suryanto Hertika; Yuni Kilawati (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ulinuha D, Andayani S, Hertika AMS, Kilawati Y. 2020. Estimation of bacterial number in the water, sediment, and biofilm of Badek and Mewek River (Malang, Indonesia) using Plate Count and eDNA Method. Biodiversitas 21: 3832-3836.  Several methods have been developed to quantify bacterial numbers in the environment, but the studies is still continued to provide the most effective and efficient method. This study was aimed to compare the capacities of two different methods (Plate Count and eDNA Method) to estimate the bacterial number in the water, sediment, and biofilm of Badek and Mewek River (Malang-Indonesia). The Plate Count Method was carried out on a Plate Count Agar (PCA) which was incubated for 24 hours at 37oC. The eDNA method was performed by slow agitation (1,800 rpm) to extract the environmental DNA of bacteria. Quantification of bacteria was obtained from the eDNA band intensity after electrophoresis in 1% gel agarose electrophoresis. Smartladder was used as a marker for the eDNA Method. The result showed that the eDNA Method was efficient for the estimation of bacterial numbers in the sediment and biofilm of Badek and Mewek River. However, this method was not suitable for estimating bacterial numbers in the water.